2013
DOI: 10.1177/2325957413488180
|View full text |Cite
|
Sign up to set email alerts
|

Learning about Barriers to Care for People Living with HIV in Egypt

Abstract: The purpose of this study was to identify obstacles health care workers face in providing care for people living with HIV and AIDS (PLWHA). Based on these findings, health authorities can design interventions to support health care workers in providing better medical care for PLWHA. Thirty in-depth interviews were conducted with physicians and nurses in one 300-bed tertiary care public hospital in Giza, Egypt. Thematic analysis was conducted by 2 investigators. Five main themes were identified (1) fear of infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 20 publications
1
19
0
1
Order By: Relevance
“…Similar to other researchers [9,21,43], we found that nurses with better HIV knowledge reported no matter what the level of education, a lower level of HIV-related stigma toward PWLH overall, and in particularly, less fear of AIDS. This finding suggested the critical role of HIV knowledge in reducing fear-based stigma [44]. Since there was no significant difference of HIV knowledge between nurses with different educational levels, HIV education should target all nurses.…”
Section: Discussionmentioning
confidence: 89%
“…Similar to other researchers [9,21,43], we found that nurses with better HIV knowledge reported no matter what the level of education, a lower level of HIV-related stigma toward PWLH overall, and in particularly, less fear of AIDS. This finding suggested the critical role of HIV knowledge in reducing fear-based stigma [44]. Since there was no significant difference of HIV knowledge between nurses with different educational levels, HIV education should target all nurses.…”
Section: Discussionmentioning
confidence: 89%
“…who inject illegal drugs, homosexual men and sex workers with medical services due to their immoral actions. 21 The intervention slightly improved this stigmatizing attitude through focusing on the patients' right of treatment irrespective of their moral behavior. Regarding the effect of intervention on HIV stigma and discrimination among health care providers towards pregnant women living with HIV, the study revealed attitudes reflecting violation of the patient's ethical rights of strict confidentiality and informed consent because of her HIV status before and even after intervention which reinforced these patient's rights.…”
Section: Discussionmentioning
confidence: 99%
“…An Egyptian study of 30 doctors and nurses using in-depth interviews provided some information about the constraints of providing care for people living with HIV (PLHIV) which also likely to be relevant for settings with low HIV prevalence and limited resources such as in the MENA region. The study revealed fear of infection stemming from misconceptions and lack of knowledge of modes of HIV transmission and infection control systems (Abdelrahman et al 2015). A study from Jordan also reported discriminatory behaviors such as denial of care and fear of infection among health care workers when dealing with PLHIV, mostly as a result of a lack of knowledge and misconceptions about modes of transmission (Hassan and Wahsheh 2011).…”
Section: Health Challenges Of Women Living With Hiv In Menamentioning
confidence: 96%
“…Reluctance to treat PLHIV can largely be explained by the belief of respondents that PLHIV will die soon and that they have no need for medical services. Respondents also feared being stigmatized by family, colleagues, and clients and by the community at large (Abdelrahman et al 2015).…”
Section: Health Challenges Of Women Living With Hiv In Menamentioning
confidence: 99%